Performance analysis of proposed solar HDH water desalination systems for hot and humid climate cities. (5th November 2018) - Fouda, A.; Nada, S.A.; Elattar, H.F.; Rubaiee, Saeed; Al-Zahrani, A.
Highlights: Three proposed solar powered humidification–dehumidification (HDH) water desalination systems are investigated and presented. Parametric study of the hourly and daily systems performance is presented at various operating parameters. Mathematical model of the HDH water desalination system is developed and solved numerically using EES software. The performance of the proposed systems is maximized by changing between the open/closed mode of operations. Abstract: Transient performance analysis and investigation of three proposed solar powered humidification–dehumidification (HDH) water desalination systems: single stage (SS), double stages (DS) and modified double stages (MDS) systems are presented for hot and humid cities. Open/closed modes of operations of the systems are also investigated. A parametric study of the hourly and daily systems performance is presented at various operating parameters. The results reveal that: (i) inserting solar collectors in HDH systems for air and water heating substantially enhances the system's performance; (ii) the fresh water productivity of all systems at open mode of operation increases with increasing the outdoor air temperature and humidity; (iv) at low outdoor humidity, the system's performance at closed mode of operation is higher than those at open mode of operation and the opposite is true at high outdoor humidity; (v) comparing between the three systems, MDS system (open mode) can produce fresh water of 350 kg/day with GORday of 1.63 and its fresh water productivity enhances with 86.7% and 34% than SS and DS systems, respectively; and (vi) using control system, the performance of the proposed systems can be maximized by changing between the open/closed mode of operations according to the outdoor conditions.